The Effectiveness of Nusa Board Media on Student Learning Outcomes at Dahlanuddin SD Surabaya - Nur Fauziah; Sri Hartatik; Nafiah; Sunanto (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
The teacher's role in creating fun learning is very influential in the dissemination of the material. If in the process of delivering learning materials the teacher is not optimal and students are less interested in receiving the material, it will affect the process of understanding students in the material presented. This study aims to determine the effectiveness of Nusa Board media on the learning outcomes of class I students at SD Dahlanuddin Surabaya. This study uses a quantitative approach with the One Group Pretest-Posttest method. The subjects of this study were the first-grade students of SD Dahlanuddin Surabaya. Data collection techniques using tests in the form of pretest and posttest. The data analysis techniques used were instrument analysis, validity test, reliability test, assumption test using One-Sample Kolmogorov-Smirnov test, and paired T-test hypothesis test. The results of this study indicate that there is a difference in student learning outcomes before and after the implementation of Nusa Board media with an average pretest score of 66.8 and an average posttest score of 86.25. The increase in the average score of students is also evidenced from the results of the statistical test output analysis of the paired T-TEST (2 tailed) test which shows sig (2.tailed) 0.000 < 0.05. It can be concluded that hypothesis 1 is accepted, which means that there is a difference between the learning outcomes on the score pretest and posttest, and it can be concluded that the Nusa Board media is effective in improving the learning outcomes of first grade students at Dahlanuddin Elementary School Surabaya.